Sensor fusion of electronic nose and electronic tongue for classification of Orthosiphon stamineus - Azmi, Zakaria; Ali Yeon, Md Shakaff, Prof. Dr.; Abdul Hamid, Adom, Assoc. Prof. Dr.; Mansur N., Ahmad; Abd. Razak, Shaari; Mahmad Nor, Jaafar, Prof. Madya; Abu Hassan, Abdullah; Nazifah A., Fikri; Latifah Munirah, Kamarudin (American Scientific Publishers, 2011)
Link to publisher's homepage at www.aspbs.com/